Identification of point defects on Co-Ni codoping in SnO2 nanocrystals and their effect on the structural and optical properties - Roy, S.; Prajapati, B.; Singh, A.; Joshi, A.G.; Chatterjee, S.; Ghosh, A.K. (American Institute of Physics Inc., 2019)
Sn 0.97 - yCo 0.03Ni yO 2 (0 ≤ y ≤ 0.04) nanocrystals, with the average crystallite size in the range from 7.3 nm (for y = 0.00) to 5.6 nm (for y = 0.04), have been synthesized using a pH-controlled chemical coprecipitation technique. All the nonstoichiometric and stoichiometric point defects arising in the nanocrystals on codoping have been identified, and their effect on structural and optical properties of the nanocrystals have been extensively studied. It has been observed, using X-ray photoelectron spectroscopy (XPS), that on increasing the Ni codoping concentration (y), the nonstoichiometric Sn defect, Sn Sn ″, increases in compensation of the existing defect Sn i ⋯ for y = 0.00 nanocrystals. High-resolution transmission electron microscopy also confirms the existence of Sn Sn ″. Regarding the stoichiometric Frenkel defect, XPS results have indicated that the concentration of V O and O i, manifested in the form of dangling bond related surface defect states, increases with increase in y. Temperature dependent magnetization measurements of the nanocrystals confirm the charge state of V O. The point defects have been found to affect the structural properties in a way that the distortion in the octahedral geometry of a complete Sn-O octahedron effectively reduces, whereas the distortion in the trigonal planar coordination geometry of oxygen increases. A direct effect of the O related Frenkel defect has been observed on the blue luminescence of the nanocrystals such that the spectral contribution of blue luminescence in the total emission intensity increases by ≈ 72% for y = 0.04 as compared to y = 0.00. © 2019 Author(s).
Keywords: Co-Ni codoping; SnO2; nanocrystals; optical properties